Marketing Research of Supply and Demand in the Regional Energy Market - M. A. Alinazarova (Статистика и экономика, 2022)
The study is devoted to the energy market of the Sughd region of the Republic of Tajikistan. The features of marketing in the energy sector are highlighted and the authors’ interpretations of the definition of “marketing” in the energy sector are given. The functions of marketing activities in the development of the energy sector of the region are considered. Examples of the correlation between supply and demand for energy products, including electricity, are given for further forecasting the consumption of these products. The ratio analysis of supply and demand of electricity in a certain area was carried out. To identify factors affecting the demand of electricity consumers, an analysis was carried out using statistical and mathematical calculation methods. As a result, a factor that has a greater influence on the demand of electricity consumers has been identified. The ways of solving marketing research for the further successful functioning of the energy company in the interests of society and the social well-being of the population are proposed.Purpose of the study. The purpose of this paper is to study the state of the regional energy market on the basis of marketing research that characterizes the activities of an energy company; identification of indicators such as consumer dissatisfaction with energy products. The paper is based on a dynamic analysis of analytical and statistical information about ongoing processes in the energy sector. The task is to conduct marketing research of supply and demand in the regional energy market.Materials and methods. The information base of the study is analytical information and statistical data on indexes of supply and demand for energy products, including electricity. The methodological basis of the study is represented by statistical methods of information analysis: comparative analysis and analysis of time series.Results. Based on the results of an economic and statistical analysis of consumer demand indicators for the use of energy products, including electricity, factors influencing demand have been identified. Of the three selected factors, it is especially worth noting the demand of consumers using electricity, which are population density indexes, weather conditions and the number of rainfall days in a particular region, it is theoretically established that population density is a more influential index.Conclusion. Energy is the main branch of the national economy of the country, which contributes to the development of the economy and the normal life of the population. Until now, the problem of providing the population and the national economy of the regions of the republic with energy goods and electricity makes us think about new ways to solve the problem. Since hydroelectric power generation in the country is the share of hydroelectric power plants, given the economic and social condition of the country in the power supply system, it will be appropriate to create a marketing system platform.